EFFECTIVE COMMUNICATION STRATEGIES IN BUSINESS NEGOTIATIONS IN THE UMKM SECTOR - Muh. Husriadi; Citra Ayu Ningsi; Usman. M (Adisam Publisher, 2025)
This research departs from problem low the effectiveness of communication strategies in business negotiations in the MSME sector which impacts the results negotiation and competitiveness business. The aim of the research is to identify and analyze communication strategies effective in MSME negotiations as well its implications for business development. The method used is qualitative with a case study design, involving interview in-depth, observation, and documentation analysis. The research results found that personal and direct communication, the use of digital media in an intensive, as well as innovation in packaging narrative- like messages persuasiveness is a factor main success MSME negotiations. This innovation strengthens emotional bonding with business partners and increases persuasive power. The implications of this research emphasize importance training interpersonal and digital communication, as well as the development of adaptive communication strategies to support the sustainability and growth of MSMEs in the dynamic digital era.